Real-time kinematic positioning using fused data from multiple GNSS antennas - Li, Bofeng; Teunissen, Peter (International Society of Information Fusion, 2012)
Array-aided precise point positioning (A-PPP) is a nonlinear estimation concept that uses Global Navigation Satellite System (GNSS) data, from multiple antennas of known local geometry, to realize improved integer ambiguity resolution thus enabling faster and improved positioning. In this contribution, we demonstrate the performance of A-PPP for long-baseline Real-Time Kinematic (RTK) positioning using dual-frequency GPS data collected on a 80 km baseline and we compare the results with conventional RTK. We formulate the underlying multivariate, integer and orthonormality constrained, GNSS model and show how the array-antenna data is fused to enable improved long-baseline RTK positioning.